The Role of Marriage Agreements in Separation of Assets in Mixed Marriages Between Indonesian Citizens (WNI) and Foreign Citizens (WNA) - Shoniya Dwi Putri Shabrina; Henry Aspan; Fitri Rafianti (CV. Era Digital Nusantara, 2026)
Mixed marriages between Indonesian citizens (WNI) and foreign nationals (WNA) have seen a significant increase year by year. This phenomenon can lead to various legal issues, one of which concerns the separation of property in marriage to protect the constitutional rights of Indonesian citizens, particularly regarding land ownership. A prenuptial agreement is a legal tool that couples can use to arrange the separation of property in a legitimate and written manner. The purpose of this research is to analyze the role of prenuptial agreements in the separation of property for mixed couples, especially in the context of protecting property rights and legal certainty. The method used is normative legal research with a legislative approach, utilizing data sources in the form of laws and regulations, particularly Law No. 1 of 1974 concerning marriage. The analysis results indicate that prenuptial agreements are crucial in avoiding the commingling of assets, especially to protect the ownership of Indonesian citizens over immovable assets, which are restricted by the Basic Agrarian Law. In mixed marriages, such situations can disadvantage Indonesian citizens regarding land ownership rights, which would become joint property. According to Law No. 5 of 1960 on the Basic Agrarian Law (UUPA), it is stated that foreign nationals are not allowed to own land in Indonesia. As regulated in Article 29 of the Marriage Law, it provides a solution through property separation that can offer protection for Indonesian citizens to safeguard their land ownership rights and assets. The implementation of prenuptial agreements in mixed marriages still faces many challenges, one of which is the insufficient role of notaries and marriage registration institutions in providing education to couples intending to marry. Therefore, there is a need for stronger legal education to support the effectiveness of prenuptial agreements in legal practice in Indonesia. This research concludes that prenuptial agreements play a very important role in providing legal protection for mixed marriages between Indonesian citizens and foreign nationals in the mechanism of property separation. The property separation agreement not only protects the constitutional rights of Indonesian citizens over land but also helps avoid potential legal conflicts that may arise in the future